1995
DOI: 10.1002/sce.3730790306
|View full text |Cite
|
Sign up to set email alerts
|

When science is “another world”: Relationships between worlds of family, friends, school, and science

Abstract: The purpose of this article is twofold: to describe a model for understanding how students' responses to science are related to the degree of congruency between their worlds of family, friends, school, and science; and to explore the implications of this model for practice and policy in science education. The study focuses on the meaning-perspectives of students to understand how they differentially experience school science. On the basis of classroom observations, teacher recommendation, and students' willing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
185
1
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(202 citation statements)
references
References 10 publications
5
185
1
11
Order By: Relevance
“…In many ways, our analyses confirmed findings from previous surveys, as well as being consistent with other work around aspirations and participation in science (c.f. Archer & DeWitt, 2016;Costa, 1995;Gilmartin et al, 2006). For instance, the data highlighted the small proportion of students with high levels of science capital (who are, critically, also most likely to want to pursue science in the future).…”
Section: Discussionmentioning
confidence: 99%
“…In many ways, our analyses confirmed findings from previous surveys, as well as being consistent with other work around aspirations and participation in science (c.f. Archer & DeWitt, 2016;Costa, 1995;Gilmartin et al, 2006). For instance, the data highlighted the small proportion of students with high levels of science capital (who are, critically, also most likely to want to pursue science in the future).…”
Section: Discussionmentioning
confidence: 99%
“…Students success in science depends on the degree of cultural difference students perceive between their life-world and science classroom; how effectively students move between their life-world culture and the culture of science or school science; and, the assistance students receive in making those transition easier (Jegede & Aikenhead, 1999;Costa, 1995;Jegede, 1995;Phelan, Davidson & Cao, 1991). The interaction between students' life-world culture and culture of school science may be conflicting, and may lead to a painful cognitive conflict which students want to overcome.…”
Section: Towards the Achievement Of A Unified …mentioning
confidence: 99%
“…Although Subotnik et al (2011) presented a comprehensive review based on psychological science that proposed a direction forward to re-thinking gifted education and giftedness, however it was found that the authors overlooked the relevant cultural aspects of gifted education. It is evident that both general and gifted students representing diverse cultural backgrounds regularly encounter cognitive conflicts which affect their learning of sciences (Aikenhead, 2000;2001;Costa, 1995;Jegede, 1995;Jegede & Aikenhead, 1999;Phelan, Davidson & Cao, 1991). And this situation will inevitably impact on the development of psychosocial skills among gifted students who are particularly from culturally diverse backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…대표적인 도구로 는 Simpson과 Troost가 개발한 Simpson-Troost Attitude Questionnaire(STAQ) 척도가 있었다 (Aikenhead, 1996;Costa, 1995;Phelan et al, 1991 . 이 도구는 5점 척도로 구성된 22문항으로 이루어져 있으며 과학에 대한 흥미(science is fun for me), 동료(peer models), 과학 수업에 대한 동기 (motivation in school), 자신의 노력(self-directed effort), 가족(family models)이라는 5개의 하위 요 인으로 구성되어 있다.…”
Section: ) 국내 연구 동향unclassified